Turmeric - maize and onion intercropping systems II. Leaf area index and dry matter accumulation - PALANIAPPAN, K SIVARAMAN, S P (Journal of Spices and Aromatic Crops, 1995)
Experiments were laid out at Bhavanisagar and Coimbatore (Tamil Nadu, India) to study the influence of intercropping on leaf area index and dry matter accumulation in whole plants of turmeric (Curcuma longa), maize (Zea mays) and onion (Allium cepa) when grown in intercropping and sole cropping systems. Maize was intercropped with turmeric in two proportions (50 and 100 per cent of the recommended population levels). Onion was also introduced as additional intercrop with maize with 23 per cent of the population of sole crop. These crops were also raised as sole crops. Leaf area indices and dry matter accumulation of maize and turmeric at different stages were influenced significantly by intercropping systems, in both locations. Intercropping maize in turmeric significantly reduced the growth of the latter. This effect was quite obvious where maize was raised as intercrop at 100 per cent of the recommended population. Sole cropping of turmeric resulted in higher leaf area indices than turmeric raised as intercrop. Raising onion as additional intercrop did not influence dry matter accumulation of component crops appreciably.